CAD Representation of the Mullins Effect from the SEGE 80 Flexible Coupling Model - Stefan Tenev; Ismail Mehmedov; Aleksandrina Bankova; Nina Nedeva; Stefan Stefanov; Rosen Hristov; Asparuh Atanasov; Plamen Nikolov; Svetoslav Petrov (Engineering Proceedings, 2024)
A Mullins simulation was conducted to analyze the effects of loading and unloading of a flexible-type SEGE coupling with a nominal torque of <semantics>Tnom=80<mtext> </mtext>Nm</semantics> and maximum torque of <semantics>Tmax=120<mtext> </mtext>Nm</semantics>. The coupling’s properties were determined by examining its moment characteristics at <semantics>T=120,<mtext> </mtext>100,<mtext> </mtext>80,<mtext> </mtext>60,<mtext> </mtext>40,<mtext> </mtext>and<mtext> </mtext>20<mtext> </mtext>Nm</semantics>. The correlation between the Mullins effect results obtained from the SEGE coupling load simulation via SolidWorks 2022 software and the actual experimental data was examined.